The Strategies used by Tunas Mekar School to Teach Autistic Children in Primary School English as A Second Language - Rr, Rr. Retno Dwi Susanti (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2024)
Abstract: The objective of this study is to find autistic children use to learn English and understand how to teach English to autistic students at this elementary school. The qualitative research method was applied in this investigation. Qualitative mining yields detailed and unpredictable findings. In this instance, the principal, an English teacher, a physicist, autistic children from various backgrounds, and shadow teachers all took part in the investigation process. Tools included observations and interviews with teachers, a physicist, a shadow teacher, an English teacher, and a principal. Tunas Mekar School has the following six plans: The acronym ABA represents "Taking Control of Students' Actions." Modelling and role-playing are utilized to teach through movement and facial emotions. Less is more (with clear, simple instructions). To enhance the child's social skills in the classroom, assist them with visual materials and provide them with a range of stimuli. Employing PECS, being ability to obey instructions while maintaining composure is a sign of self-control. Learning a foreign language also benefits children with ASD by increasing their self-awareness. To organize and get along with others, parents should emphasize their child's talents and provide an organized learning environment.